Dans les soutes de la mondialisation : les insécurités langagières des travailleurs d’en bas - Adami, Hervé (Neofilolog, 2023)
In the great upheavals of globalization, this article will focus on those who are not directly involved in this great movement. These include migrants. For them, the most useful language is that of survival, both social and professional. In this context, we will focus on the training demands that emanate from certain professional fields in France, formulated in the urgency of economic and human situations that concern the public employment actors, the training structures and of course the learners/workers themselves. Indeed, certain economic sectors are under pressure, in the sense that they are struggling to recruit. Recourse to migrant labour is therefore one of the solutions, but, in most cases, the question of mastering the language of the host country in oral and/or written form arises,. Didactic solutions must be found on a case-by-case basis, in a very precise and specific way. In order to describe and analyse this situation, the article will be based on two experiences of technical and linguistic training in two vocational training fields: i) catering and ii) building and public works.